Urgency of Law Amendment as Foundation of The Implementation of Cyber Notary - Devi Alincia; Tundjung Herning Sitabuana (LAW REFORM, 2021)
The concept of Cyber Notary in Indonesia is influenced by the advance of technology, the need of the society, and the way people think. Cyber notary is mentioned in the amended Law on Notary (Amended UUJN) in the form of other authorities, which is to certify transaction made electronically (cyber notary). However, in the level of legal practice, cyber notary’s authority is not performed effectively by notaries in real practice. This study aimed to examine the aspect of legal certainty of cyber notary and how far the chance of UUJN’s Amendment is able to provide certainty for the implementation of cyber notary. This study was conducted using normative legal research method, a descriptive method, through statute approach and history approach. The result of this research shows that: first, notary’s authority in cyber notary is merely to legalize an electronic document and privately made deed. The second, the certification of a transaction which is done electronically (cyber notary) by Notary has validity or legally valid and is not against the principle of Tabellionis Officium Fidelliter Exercebo because during the process notaries is present directly. Based on the result of this study, the suggestion that can be given is that it is necessary to amend UUJN and to formulate implementing regulation of the mechanism of notary’s authority to certify electronic transaction.